GPM dan OPM terhadap Harga Saham - Riki Firmansyah; Nursito Nursito (Journal of Management and Bussines (JOMB), 2022)
This study was conducted with the aim of knowing the effect of Gross Profit Margin (GPM) and Operating Profit Margin (OPM) partially or simultaneously on Stock Prices in Pulp and Paper Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The research method used is descriptive verification with data analysis using Multiple Linear Regression analysis. The technique used to determine the sample in this study is purposive sampling and obtained 7 companies during 4 years of research. The results of the study show that partially GPM and OPM have an effect on stock prices. Simultaneously GPM and OPM have an effect on stock prices. In conclusion, GPM and OPM partially and simultaneously affect stock prices in manufacturing companies in the pulp and paper sub-sector. Keywords: GPM, Stock Price, OPM